Issues and challenges of Fischer–Tropsch synthesis catalysts - Amin, Muhammad; Usman, Muhammad; Kella, Tatinaidu; Khan, Wasim Ullah; Khan, Imtiaz Afzal; Hoon Lee, Kang (Frontiers in Chemistry, 2024)
Depletion of oil and gas resources is a major concern for researchers and the global community. Researchers are trying to develop a way to overcome these issues using the Fischer–Tropsch synthesis (FTS) process. The FTS reaction converts a mixture of hydrogen and carbon monoxide gases into a liquid fuel. The reactions are performed in the reactor and in the presence of a catalyst. A series of catalysts, such as iron, cobalt, nickel, and ruthenium, have been used for the FTS process. In iron-based catalysts, the Fe5C phase is the active phase that produces C5+ hydrocarbons. At higher conversion rates, the presence of water in the products is a problem for cobalt catalysts because it can trigger catalyst deactivation mechanisms. Ni-based catalysts play key roles as base catalysts, promoters, and photothermal catalysts in FTS reactions to produce different useful hydrocarbons. Ruthenium catalysts offer not only high activity but also selectivity toward long-chain hydrocarbons. Moreover, depending on the Ru particle size and interaction with the oxide support, the catalyst properties can be tuned to enhance the catalytic activity during FTS. The detailed reaction pathways based on catalyst properties are explained in this article. This review article describes the issues and challenges associated with catalysts used for the FTS process.